Changes in severity of problem gambling and subsequent suicide attempts: a longitudinal survey of young adults in Great Britain, 2018–20. (March 2023) - Wardle, Heather; Kesaite, Viktorija; Tipping, Sarah; McManus, Sally
Summary: Background: Cross-sectional studies identify problem gambling as a risk factor for suicidality. Using an online longitudinal survey, we aimed to examine the association between changes in severity of gambling behaviour and attempted suicide. Methods: The Emerging Adults Gambling Survey is a longitudinal survey of people in England, Scotland, and Wales, aged 16–24 years interviewed online between June 25 and Aug 16, 2019 (wave 1) and 1 year later between July 13 and Oct 8, 2020 (wave 2). The Problem Gambling Severity Index (PGSI) was administered at both waves. Multivariable logistic regression models examined wave 1 PGSI score and between-wave change in PGSI score as risk factors for suicide attempts at wave 2, unadjusted and with adjustment for wellbeing, anxiousness, impulsivity, perceived loneliness, and suicide attempts at wave 1. Findings: 3549 participants were interviewed in wave 1 and 2094 were interviewed in wave 2, of whom 1941 were included in this analysis (749 [39%] men; 1192 women [61%]). Prevalence of attempted suicide did not change between waves (wave 1: 3·7% [95% CI 2·9–4·8], n=75; wave 2: 3·3% [2·5–4·3], n=65). 78·9% (95% CI 76·7–80·9, n=1575) of participants had stable PGSI scores between the two waves, 13·7% (11·9–15·6, n=233) of participants had a decrease in PGSI score by 1 or more, and 7·5% (6·2–8·9, n=133) had an increase in PGSI score by 1 or more. An increase in PGSI scores over time was associated with suicide attempt at wave 2, even with adjustment for baseline PGSI score and other factors (adjusted odds ratio 2·74 [95% CI 1·20–6·27]). Wave 1 PGSI score alone was not associated with suicide attempt at wave 2 in fully adjusted models. Interpretation: Repeated routine screening for changes in gambling harm could be embedded in health, social care, and public service settings to allow effective identification and suicide prevention activities among young adults. Funding: Wellcome Trust.